Memorandum on Social Dynamics & Social Welfare - Planning Commission (Planning Commission, 1960)
The 1960 Memorandum on Social Dynamics and Social Welfare synthesizes findings from multiple research studies sponsored by the Planning Commission of India to inform social policy formulation for the Third Five-Year Plan. The report examines a wide range of social issues affecting marginalized groups, including beggary, prostitution, ex-criminal tribes, women’s employment, caste relations, and cultural change among tribal communities. It highlights the deep interconnections between poverty, social disorganization, gender inequality, and entrenched traditions, emphasizing that economic deprivation and weak institutional support are central to many social problems. The memorandum advocates comprehensive rehabilitation, preventive education, employment generation through cottage industries and cooperatives, and culturally sensitive welfare interventions. Overall, it underscores the need for scientifically informed, context-specific social welfare strategies to promote inclusive development and advance India’s transition toward a comprehensive welfare state.
Prepared for the Research Programmes Committee of the Planning Commission (Government of India)
Prepared for the Research Programmes Committee of the Planning Commission (Government of India)
Keywords: Social Dynamics; Social Welfare Policy; Planning Commission of India; Marginalized Communities; Beggary Studies; Prostitution and Rehabilitation; Women’s Employment; Gender Inequality; Tribal Cultural Change; Caste Relations; Community Development; Third Five-Year Plan